THE IMPACT OF RISK-BASED PERFORMANCE AUDIT ON IMPROVING CORPORATE GOVERNANCE - Fildzah Shabrina; Rimba Shimanjuntak; Nur Azizah; Yulisfan; Ismail (Yayasan Multidimensi Kreatif, 2025)
This study analyzes the impact of risk-based performance audit on improving corporate governance through a systematic literature analysis. Efficient corporate governance is a very important foundation for the sustainability and performance of companies in the ever-changing business environment. Performance audit as a monitoring tool has evolved by adopting a risk-based approach to enhance its effectiveness and relevance. Literature references indicate that risk-based audit in performance audit has significant potential in strengthening corporate governance. The mechanisms of influence revealed include increased attention to strategic risks, strengthening internal control systems, increasing accountability and transparency, and supporting better decision-making. However, this study also notes shortcomings in existing studies, especially related to the lack of comprehensive empirical quantitative research and variations in how variables are measured. Therefore, this study not only synthesizes the existing understanding on this topic but also directs future research and provides practical implications for companies to maximize the role of risk-based performance audit in strengthening their governance framework.